2012
DOI: 10.1590/s0100-72032012001000006
|View full text |Cite
|
Sign up to set email alerts
|

Elaboração e validação de intervalos de referência longitudinais de peso fetal com uma amostra da população brasileira

Abstract: ResumoOBJETIVOS: Elaborar modelos de predição de peso fetal e de percentis longitudinais de peso fetal estimado (PFE) com uma amostra da população brasileira. MÉTODOS: Estudo observacional prospectivo. Dois grupos de gestantes foram recrutados: Grupo EPF (estimativa de peso fetal): pacientes para elaboração (EPF-El) e validação (EPF-Val) de um modelo de predição de peso fetal; Grupo IRL (intervalos de referência longitudinais): gestantes para elaboração (IRL-El) e validação (IRL-Val) de intervalos de referênci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The absolute error analysis between biometric tables and weight calculation formulas in which we observed the lowest error was between Furlan et al . ( 11 ) and Papageorghiou et al . ( 15 ) .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The absolute error analysis between biometric tables and weight calculation formulas in which we observed the lowest error was between Furlan et al . ( 11 ) and Papageorghiou et al . ( 15 ) .…”
Section: Resultsmentioning
confidence: 96%
“…The absolute error: we observed that the formula by Furlan et al . ( 11 ) and biometry by Papageorghiou et al . ( 15 ) had the smallest errors (zero), as shown in Tab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal growth: the estimated fetal weights (EFWs) were calculated using Bennini's formula and interpreted according to local conditional reference intervals of weight. 19 Fetal growth restriction (FGR) was defined as a progressive and evident change in the pattern of growth towards the inferior limits of these intervals, even if not reaching values below the 10 th centile. 2.…”
Section: Methodsmentioning
confidence: 99%